Inhibition of DNA damage repair by the CDK4/6 inhibitor palbociclib delays irradiated intracranial atypical teratoid rhabdoid tumor and glioblastoma xenograft regrowth - Hashizume, Rintaro; Zhang, Ali; Mueller, Sabine; Prados, Michael D.; Lulla, Rishi R.; Goldman, Stewart; Saratsis, Amanda M.; Mazar, Andrew P.; Stegh, Alexander H.; Cheng, Shi-Yuan; Horbinski, Craig; Haas-Kogan, Daphne A.; et al. (Neuro-oncology (Charlottesville, Va.), 2016)
Radiation therapy is the most commonly used postsurgical treatment for primary malignant brain tumors. Consequently, investigating the efficacy of chemotherapeutics combined with radiation for treating malignant brain tumors is of high clinical relevance. In this study, we examined the cyclin-dependent kinase 4/6 inhibitor palbociclib, when used in combination with radiation for treating human atypical teratoid rhabdoid tumor (ATRT) as well as glioblastoma (GBM). Evaluation of treatment antitumor activity in vitro was based upon results from cell proliferation assays, clonogenicity assays, flow cytometry, and immunocytochemistry for DNA double-strand break repair. Interpretation of treatment antitumor activity in vivo was based upon bioluminescence imaging, animal subject survival analysis, and staining of tumor sections for markers of proliferation and apoptosis. For each of the retinoblastoma protein (RB)-proficient tumor models examined (2 ATRTs and 2 GBMs), one or more of the combination therapy regimens significantly (P < .05) outperformed both monotherapies with respect to animal subject survival benefit. Among the combination therapy regimens, concurrent palbociclib and radiation treatment and palbociclib treatment following radiation consistently outperformed the sequence in which radiation followed palbociclib treatment. In vitro investigation revealed that the concurrent use of palbociclib with radiation, as well as palbociclib following radiation, inhibited DNA double-strand break repair and promoted increased tumor cell apoptosis. Our results support further investigation and possible clinical translation of palbociclib as an adjuvant to radiation therapy for patients with malignant brain tumors that retain RB expression.